A wide skull ostelytic metastasis in advanced breast cancer - Buti, Sebastiano; Palumbo, Anselmo Alessandro; Sikokis, Angelica (Acta Biomedica Atenei Parmensis, 2014)
We present a case report of a large and deep osteolytic metastasis radiological documented involving the skull in a woman affected by advanced breast cancer during endocrine therapy